Irving Howe : socialist, critic, Jew - Alexander, Edward, 1936- (Jewish literature and culture., 1998)
For over fifty years, from the 1940s to the 1990s, Irving Howe was a commanding, if controversial, figure in American intellectual life. Writing with the productivity of a major industry, Howe took on issues ranging from left-wing politics and American writers to Yiddish literature, the State of Israel, the condition of the American academy, and New York cultural and literary life. Best known for his prize-winning history of American Jewish immigrant culture, World of Our Fathers, Howe was an outspoken socialist as well as founder and editor of the democratic socialist magazine Dissent. Through a clear, eloquent, and forcefully argued study of Howe's politics, writings, and thought, Edward Alexander constructs a sympathetic yet critical intellectual biography of this complex individual.